The Basic Motion Learning Model of Small Game Based Throwing in Elementary School - Gunawan Setiawan; Syamsuramel Syamsuramel; Silvi Aryanti (Journal Physical Education, Health and Recreation, 2021)
This study aims to develop a small game-based basic motion learning model at Elementary School Number 65 Rejang Lebong. The research method used is research and development (R&D) using ten stages from Borg and Gall. The research instruments used were locomotor, non-locomotor tests, and manipulative basic movement skills tests. The treatment in this study was in the form of a basic motion learning model based on small games given for 4 weeks. The subjects in this study were students in grades 4 and 5 of Elementary School Number 65 Rejang Lebong. Subjects in this study were 30 people. The validation results obtained in small-scale trials regarding the quality of the learning model have entered into the validation criteria filled by the validator with a percentage of 63% and the results of large group trials are declared valid with a percentage of 81.25% which means very feasible. Furthermore, the effectiveness test was carried out using the t-test. In the significance test of the difference using the SPSS tool, the mean value = 0.8666 which shows the difference between the pre-test and post-test results, the results of T-count = 13.730, df = 29, and P-Value = 0.000 <0.05, which means that there are There is a significant difference between before and after being treated with the small game-based learning model of throwing basic motion learning. Where the post-test results have positive results with a significant difference compared to the pre-test results. So that the learning model of the basic motion of throwing based on small games can be used in learning physical education and health in elementary schools. The implication of this research is that the basic motion learning model of throwing based on small games can be used as a form of learning the basic motion of throwing in elementary school children.